Perancangan panduan desain produk fesyen untuk mata kuliah berbasis studio di masa pandemi Covid 19: Studi kasus mata kuliah Visual Study di Universitas Ciputra - Rahayu Budhi Handayani; Enrico Enrico; Dewa Made Weda Githapradana (Institut Seni Indonesia Yogyakarta, 2022)
The Covid 19 pandemic has an impact on the studio-based learning process as well as on the Visual Study course, which is one of the core courses in the Fashion Product Design study program in Universitas Ciputra Surabaya. The course has learning outcomes, that is ‘students are able to independently design creative and distinctive fashion works by applying fashion design methods through in-depth visual observation, direct and indirect exploration’. Apart from the absence of direct field observations, the concept of studio-based learning with active learning methods with lots of interactions between teachers and students cannot be done at this time. The design of a guide is needed to assist students in designing fashion products so that the learning outcomes of this course can be achieved. Qualitative descriptive research with digital ethnography was carried out in this study in order to respond directly to the Covid 19 pandemic which has an impact on design-based and studio-based learning. The results of this study are a lesson plan, design guide, and a learning management system which is the result of a needs assessment and is evaluated at the end of the semester to see the success of the designed guide.